Ending water scarcity in Sri Lanka dry zone. (Metro Manila, Philippines Asian Development Bank, 2017)
This brief discusses ADBs project supporting a major government water resources project in Sri Lanka to divert untapped water from the Mahaweli River.
Keywords: Agricultural resources -- Sri Lanka; Agriculturee -- Economic aspects -- Sri Lanka; Electronic books